Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.2137/145960607784125366
|View full text |Cite
|
Sign up to set email alerts
|

Economic and environmental performance of alternative policy measures to reduce nutrient surpluses in Finnish agriculture

Abstract: This paper provides an economic sector level analysis of the effectiveness of different policy measures in decreasing nitrogen (N) and phosphorus (P) surpluses from agriculture in order to reduce nutrient runoff from agricultural fields to watercourses and to improve water quality of surface waters. Assuming no changes in the EU level policies after CAP reform 2003 we focus on national level policy measures such as full or partial de-coupling of national support from production, payments for reduced nutrient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…For farmers who operate on farms that are plant production oriented, adoption was more likely but the parameter was only statistically significant in model 2. Although livestock farms are associated more with nutrient run off, income support through AES is more vital for plant production farms (Lehtonen et al, 2007) justifing their higher tendency to participate. The appraisal of information was found to be a significant and positive determinant of adoption, as expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For farmers who operate on farms that are plant production oriented, adoption was more likely but the parameter was only statistically significant in model 2. Although livestock farms are associated more with nutrient run off, income support through AES is more vital for plant production farms (Lehtonen et al, 2007) justifing their higher tendency to participate. The appraisal of information was found to be a significant and positive determinant of adoption, as expected.…”
Section: Resultsmentioning
confidence: 99%
“…Also, is a 1 Agri-environmental scheme (AES) in Finland is based on a three level system, i.e mandatory basic measures, additional measures and special measures (Lehtonen et al, 2007). Its main goal is to reduce nutrient runoff and maintain agricultural landscape as well as biodiversity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Such changes in N use associated with yield declines correspond to 2.5 and 4.8 %, respectively (Ylätalo 1996). Lehtonen et al (2007) applied the same functions after calibrating them with more recent data and got similar results for all cereals. It was concluded that the major price changes experienced in Finland after 1995 resulted in no greater than 5 % total reduction in cereal yields, according to short-term, farmlevel profit-maximization variable costs and returns.…”
Section: Introductionmentioning
confidence: 83%
“…In 1995, when Finland joined the European Union, crop prices decreased by 40 to 60% and fertiliser prices by approximately 10%, and a large scale Agri-Environment Programme (AEP) was launched. Lehtonen et al (2007), however, concluded that the major price changes experienced in Finland after 1995 resulted in total reductions in cereal yields of no more than 5%, due to the short-term farm-level profit maximisation based on variable costs and returns. The AEP provided a stable €93−120 per ha support payment, on the top of Common Agricultural Policy (CAP) Pillar 1 (€150-240 per ha, depending on region) and Least Favourable Area (LFA) payments (averaging €250 per ha), for those farmers who committed to comply with the N fertiliser limits and other conditions of the AEP.…”
Section: Agro-management Effects On Yield Trendsmentioning
confidence: 99%